2021
DOI: 10.1038/s41598-021-00676-x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a murine model of endothelial dysfunction induced by chronic intraperitoneal administration of angiotensin II

Abstract: Endothelial dysfunction (ED) is a key factor for the development of cardiovascular diseases. Due to its chronic, life-threatening nature, ED only can be studied experimentally in animal models. Therefore, this work was aimed to characterize a murine model of ED induced by a daily intraperitoneal administration of angiotensin II (AGII) for 10 weeks. Oxidative stress, inflammation, vascular remodeling, hypertension, and damage to various target organs were evaluated in treated animals. The results indicated that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 59 publications
1
5
0
Order By: Relevance
“…In this work, we demonstrated the efficacy of the hydroalcoholic extract of S. edule roots in controlling the pathological conditions that often accompany NASH, such as hepatomegaly, hypertriglyceridemia, and adipose tissue enlargement, effectively controlling triglyceride accumulation in the liver, necrosis, inflammation, and fibrosis. This study confirms the previously reported association between the chronic administration of ANGII by the i. p. route and the development of metabolic alterations in the liver (Trejo-Moreno et al, 2018, Trejo-Moreno et al, 2021.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In this work, we demonstrated the efficacy of the hydroalcoholic extract of S. edule roots in controlling the pathological conditions that often accompany NASH, such as hepatomegaly, hypertriglyceridemia, and adipose tissue enlargement, effectively controlling triglyceride accumulation in the liver, necrosis, inflammation, and fibrosis. This study confirms the previously reported association between the chronic administration of ANGII by the i. p. route and the development of metabolic alterations in the liver (Trejo-Moreno et al, 2018, Trejo-Moreno et al, 2021.…”
Section: Discussionsupporting
confidence: 92%
“…Coumaric acid, the second most abundant molecule in rSe-HA (Figure 1A), could provide the extract with antioxidant properties along with cinnamic acid (Shen et al, 2019;Anlar, 2020); the latter compound has also been shown to exert anti-inflammatory effects (Karatas et al, 2020). Both major components of rSe-HA could explain the efficacy of the extract in controlling NASH-like liver damage, as ANGII is known to induce oxidative stress and an inflammatory state (Wei et al, 2008;Trejo-Moreno et al, 2021). It should be noted that the dose used in this work is lower than those administered in studies conducted with aerial parts of the plant; previous studies used leaf or stem extracts at 0.1-0.5%, which is approximately equivalent to 1-5 g/kg (Yang et al, 2015) or 100-200 mg/kg of fruit extracts (Firdous et al, 2012); this could suggest a greater potency in root-derived extracts.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations